Remythologizing Theology Divine Acition, Passion, and Authorship - Vanhoozer, Kevin J. (Cambridge, UK ; New York Cambridge University Press, 2010)
"The rise of modern science and the proclaimed 'death' of God in the nineteenth century led to a radical questioning of divine action and authorship - Bultmann's celebrated 'demythologizing'. Remythologizing Theology moves in another direction that begi
Keywords: Bultmann, Rudolf, -- 1884-1976. Philosophical theology. God (Christianity)